Observations of surface water phytoplankton community in the Indian Ocean: A transect from tropics to polar latitudes. (August 2020) - Naik, Ravidas Krishna; George, Jenson; Soares, Melena; Anilkumar, N.; Mishra, R.K.; Roy, Rajdeep; Bhaskar, P.V.; Sivadas, Sanitha; Murukesh, Nuncio; Chacko, Racheal; Achuthankutty, C.T.
Abstract: Phytoplankton, the primary producers in all aquatic systems, plays an important role in key biogeochemical processes that are linked to higher trophic levels and climate variability. The present study deals with the phytoplankton community structure in the Indian Ocean, particularly in the higher latitudes with respect to environmental variables to understand the region specific dominant community and its governing environmental settings. The study areas were selected along the latitudinal transect between 3 o N and 53 o S (northern Indian Ocean to Indian Ocean sector of Southern Ocean). The surface water phytoplankton community based on microscopy coupled with diagnostic pigment indices showed marked variation in community structure from tropical to polar latitudes of the Indian Ocean. The Prokaryotic diagnostic pigment (ProkDP ) dominated in the Equatorial and South Equatorial regions, the Flagellate diagnostic pigment (FlagDP ) in the North Equatorial region (NER), Southern Tropical Indian Ocean and Sub-tropical Front (STF) region whereas, the Diatom diagnostic pigment (DiatDP ) dominated only at the Polar Front (PF) region. The influence of a suite of environmental variables - temperature, nutrients, salinity and mixed layer depth (MLD), on the dominant phytoplankton groups at the STF and PF was observed. This understanding of community dominance from this poorly explored area with respect to influencing factors is very vital baseline information to design the perturbation experiments in future work to understand the phytoplankton process studies of each region.